Sains Interaktif Zaman Now: Model Pembelajaran Kreatif pada Materi Biotik-Abiotik, Mitigasi Bencana, dan Tata Surya di SDI Wolowaru 5: Penelitian - Wati, Hasnah; Sariyyah, Nining; Bs, Yohana Nono; See, Siprianus; Nguru, Melkior; Gijung, Adelia Jen; Mesa, Noviliani; Ndui, Elin Febriana; Fani, Yasinta; Kune, Natalia (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
Science learning at the elementary school level often faces challenges in the form of low student interest due to conventional material delivery methods and minimal exploratory activities. This article discusses the implementation of the Modern Interactive Science model as a creative learning approach applied at SDI Wolowaru 5, with a focus on biotic-abiotic materials, disaster mitigation, and the solar system. The implementation method includes planning teaching media, implementing experiment-based learning and educational games, and evaluating student learning outcomes through observation and assessment instruments. The implementation results show an increase in student enthusiasm in participating in learning, a better understanding of science concepts, and the emergence of critical thinking skills, collaborative, and application in everyday life. It can be concluded that this interactive learning model is effective in creating a learning atmosphere that is fun, meaningful, and relevant to current educational developments.